Attentional Biases to Emotional Faces in Adolescents with Conduct Disorder, Anxiety Disorders, and Comorbid Conduct and Anxiety Disorders. Issue 3 (November 2016) - Short, Roxanna M. L.; Adams, Wendy J.; Garner, Matthew; Sonuga-Barke, Edmund J. S.; Fairchild, Graeme
Biases in emotion processing have been identified in both conduct disorder (CD) and anxiety disorders (ADs). Given the significant comorbidity between these conditions, it is important to examine whether individuals with comorbid CD+ADs display a combination of the biases observed in the non-comorbid versions of these disorders or their own distinctive pattern. We measured attentional biases and vigilance towards, and disengagement from, angry, fearful and happy faces in adolescents with CD-only (n = 31), ADs-only (n = 23), comorbid CD+ADs (n = 20) and controls (n = 30), using standard (500 ms) and masked, brief (17 ms) presentation versions of a visual-probe task. Adolescents with ADs displayed faster reaction times to happy, compared to fearful or angry, faces (irrespective of probe position). In addition to having longer reaction times in general, the CD-only and ADs-only groups showed decreased vigilance towards, and delayed disengagement from, emotional faces compared to the comorbid CD+ADs and control groups. These results suggest that CD and ADs interact in terms of their effects on vigilance and disengagement, such that attentional biases are attenuated, rather than exacerbated, in individuals with comorbid CD+ADs.